The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1023/a:1008206519571
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment with lamivudine for fulminant reactivated hepatitis B infection following intensive therapy for high-grade non-Hodgkin’s lymphoma

Abstract: Chronic carriers of Hepatitis B virus (HBV) infection, who are treated for malignant lymphoma, are at high risk of mortality from reactivated HBV infection. We report a case of a 29-year-old male chronic HBV carrier who developed fulminant reactivated HBV infection following intensive chemotherapy for stage IVB large cell B-cell non-Hodgkin's lymphoma associated with extensive central nervous system and bone marrow involvement. Prior to chemotherapy the patient had normal liver function tests and was negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
1
5

Year Published

1999
1999
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(80 citation statements)
references
References 7 publications
0
74
1
5
Order By: Relevance
“…With the increasing prevalence of HIV infection, HBV reactivation has also been observed in HBV-infected subjects with advanced immune deficiency due to HIV infection [22][23][24][25][26][27]. Hepatitis due to HBV reactivation has not only been reported in HBsAg-positive patients, HBeAg-positive [6,[28][29][30] or HBeAg-negative [31][32][33][34][35][36][37][38][39][40][41] subjects who were treated with chemotherapy and transplantation but also in HBsAg-negative patients who had past HBV infection (hepatitis B surface antibody; antiHBs positive and hepatitis B core antibody; anti-HBc positive) [42][43][44][45][46][47][48][49], especially those treated with rituximab or alemtuzumab-containing chemotherapy [50][51][52][53][54][55].…”
Section: How Important Is the Problem?mentioning
confidence: 99%
See 1 more Smart Citation
“…With the increasing prevalence of HIV infection, HBV reactivation has also been observed in HBV-infected subjects with advanced immune deficiency due to HIV infection [22][23][24][25][26][27]. Hepatitis due to HBV reactivation has not only been reported in HBsAg-positive patients, HBeAg-positive [6,[28][29][30] or HBeAg-negative [31][32][33][34][35][36][37][38][39][40][41] subjects who were treated with chemotherapy and transplantation but also in HBsAg-negative patients who had past HBV infection (hepatitis B surface antibody; antiHBs positive and hepatitis B core antibody; anti-HBc positive) [42][43][44][45][46][47][48][49], especially those treated with rituximab or alemtuzumab-containing chemotherapy [50][51][52][53][54][55].…”
Section: How Important Is the Problem?mentioning
confidence: 99%
“…As hepatitis due to HBV virological reactivation is associated or preceded by enhanced HBV viral replication during the immunosuppressive phase, the initiation of antiviral treatment such as lamivudine [102][103][104][105][106][107][108][109] and famciclovir [84,110] (Table 2). A meta-analysis of these 13 studies with 702 HBsAg-positive patients (237 treated with preemptive lamivudine and 465 untreated controls), showed that the incidence of hepatitis due to HBV reactivation was 3.3% in the treated group and 35.0% in the untreated control group (odds ratio [OR]: 0.083; 95% CI: 0.045-0.155, P \ 0.0001).…”
Section: Preemptive Use Of Nucleoside Analoguesmentioning
confidence: 99%
“…It has also recently been reported that this drug is also useful for the treatment of viral hepatitis after cytotoxic therapy. 8,9 In the present patient lamivudine appeared to work to not only avoid HBV exacerbation during transplantation, but also to treat reactivation of HBV later.…”
Section: Discussionmentioning
confidence: 75%
“…Recently, lamivudine has been successfully used in this setting, but experience is limited [11,13,18,19]. Some suggest that prompt diagnosis of hepatitis B exacerbation and early commencement of lamivudine therapy will decrease morbidity and mortality.…”
Section: Reactivation Of Hepatitis B In Patients With Chronicmentioning
confidence: 99%
“…The administration of more intensive chemotherapy in order to treat the non-responders also increases the frequency of hepatitis B flare-up [1,11].…”
Section: Introductionmentioning
confidence: 99%